Survey of waste disposal methods in Awka metropolis - US Bill; NI Chidi; CO Alisa; E Ugochukwu (Journal of Applied Sciences and Environmental Management)
Waste disposal methods commonly practiced in Awka metropolis, Anambra state were investigated from August to October, 2013. Data was analyzed with both descriptive statistics of frequency and percentages, and alternate hypotheses were tested using Analysis of Variance (ANOVA) at a significance level of 0.05. Respondents in support of open burning were 61.2 %, while 2.9 % took to burying waste as their preferred waste management option. Only about 34.0 % of the waste generated was collected at the dumpsites within the metropolis by the waste management agency, as the participants rely on their preferred waste  management options without any consideration to the associated health and environmental consequences. Statistical analysis revealed that residents of Awka believed that their waste disposal methods were safe and waste collection points were enough. The residents do not shy away from participating in disposal of waste. Majority of the respondents were of the secondary school category that engages in domestic chores.